Environmental Networks and Social Movement Theory - Saunders, Clare (Bloomsbury Academic, 2012)
Clare Saunders' book is an important contribution to the literature on social movements and the environmental movement. It opens with a broad-based consideration of the practicalities of social movement theories and it goes on to relate them to the practices of a particular movement. Theoretically and empirically rich, the book draws on extensive survey material with 144 UK environmental organizations, interviews with more than 40 key campaigners and extensive participant-observation. Saunders argues that Britain has one of the most active and well developed environmental movements in the world; it is not torn by such dramatic divisions as the US movement, yet it illustrates factions common across environmental movements in many European countries. She focuses especially on the crucial question of networking dynamics, showing that there are broad ranging network links across the movements' spatial and ideological dimensions and that this combined with inevitable ideological clashes and a degree of sectarian rivalry, helps produce the creative tension that leads the movement closer to achieving its overarching aims of protecting and preserving the environment.